C++ for everyone - Horstmann, Cay S., 1959- (Hoboken, NJ : Wiley, 2012)
'Thorough and updated coverage on all the essential C++ concepts Aimed at providing you with a solid foundation in programming with C++, this new edition incorporates programming exercises with helpful self-check questions that reinforce the concepts discussed throughout the book. You'll benefit from the how-to sections that show you how concepts are applied and advanced materials are featured on the accompanying Web site when you're ready to take your programming skills to the next level. Shows you how to use C++ to your benefit Includes advice for avoiding pitfalls Incorporates self-check questions and programming exercises to reinforce what you learn Encourages you to take your C++ programming skills to the next level with the advanced material featured on the accompanying Web site C++ for Everyone, Second Edition, is the go-to guide for getting started with C++!'
Introduction -- Fundamental data types -- Decisions -- Loops -- Functions -- Arrays and vectors -- Pointers -- Streams -- Classes -- Inheritance -- The following chapters are available online only -- Recursion (web only) -- Sorting and searching (web only) -- Lists, stacks, and queues (web only) -- Sets, maps, and priority queues (web only)
Includes index.
Keywords: C++ (Computer program language